2022
DOI: 10.1097/mop.0000000000001117
|View full text |Cite
|
Sign up to set email alerts
|

Toward greater nuance in delayed cord clamping

Abstract: Purpose of reviewFor over a decade, the International Liaison Committee on Resuscitation has recommended delayed cord clamping (DCC), but implementation has been variable due to lack of consensus on details of technique and concerns for risks in certain patient populations. This review summarizes recent literature on the benefits and risks of DCC in term and preterm infants and examines alternative approaches such as physiologic-based cord clamping or intact cord resuscitation (ICR) and umbilical cord milking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…In addition, other advances in resuscitation may be more impactful than PBCC. Consumers and policymakers may also interpret our findings as evidence that the known benefits of DCC (in relation to iron stores and neurodevelopmental outcomes) can be feasibly extended to infants who require resuscitation at birth [35].…”
Section: Plos Medicinementioning
confidence: 70%
“…In addition, other advances in resuscitation may be more impactful than PBCC. Consumers and policymakers may also interpret our findings as evidence that the known benefits of DCC (in relation to iron stores and neurodevelopmental outcomes) can be feasibly extended to infants who require resuscitation at birth [35].…”
Section: Plos Medicinementioning
confidence: 70%
“…8 Importantly, however, infants not breathing well were excluded from many of these trials. 9 Several small clinical trials have demonstrated feasibility of providing ventilatory assistance to preterm infants with intact placental circulation without identified safety concerns. [10][11][12][13] The aim of this trial was to test the hypothesis that providing assisted ventilation starting 30 seconds after birth and clamping the cord at 120 seconds, compared with delaying cord clamping for 30 to 60 seconds with breathing assistance given afterward, would reduce any grade of IVH on head ultrasonography 7 to 10 days after birth or the competing outcome of death before day 7 in extremely preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…A 2023 individual participant data meta-analysis reported that deferring cord clamping for increasingly longer periods was associated with progressively lower mortality . Importantly, however, infants not breathing well were excluded from many of these trials . Several small clinical trials have demonstrated feasibility of providing ventilatory assistance to preterm infants with intact placental circulation without identified safety concerns …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed cord clamping (DCC) [ 117 ] is recommended for both preterm [ 118 ] and vigorous term neonates [ 119 ]. In a retrospective study [ 120 ] on 796 women and their term neonates delivered by cesarean section, the authors compare the effects of early versus DCC (< 30, 30–60 and 61–120 s), on short-term neonatal hematological status (hemoglobin and hematocrit) and jaundice (transcutaneous bilirubin levels on 0 to 5 days of life and the rate of phototherapy).…”
Section: Introductionmentioning
confidence: 99%